Residual Risk of Coronary Atherosclerotic Heart Disease and Severity of Coronary Atherosclerosis Assessed by ApoB and LDL-C in Participants With Statin Treatment: A Retrospective Cohort Study - Yao, Tianci; Lu, Weilin; Ke, Jinshan; Zhang, Hao; Zhao, Xiaofang; Song, Bei; Liu, Ting; Ke, Qinmei; Liu, Chengyun (Frontiers in Endocrinology, 2022)
Background Low-density lipoprotein cholesterol (LDL-C) is the primary target of lipid-lowering therapy on the management of hypercholesterolemia in the United States and European guidelines, while apolipoprotein B (apoB) is the secondary target. To determine if elevated levels of apoB is superior to LDL-C in assessing residual risk of coronary atherosclerotic heart disease and severity of coronary atherosclerosis in participants with statin treatment. Methods This study included 131 participants with statin treatment. The generalized linear model and relative risk regression (generalized linear Poisson model with robust error variance) were used to analyze the association of the levels of apoB and LDL-C with the severity of coronary atherosclerosis and residual risk of coronary atherosclerotic heart disease. Results Categorizing apoB and LDL-C based on tertiles, higher levels of apoB were significantly associated with the severity of coronary atherosclerosis (Ptrend = 0.012), whereas no such associations were found for elevated levels of LDL-C (Ptrend = 0.585). After multivariate adjustment, higher levels of apoB were significantly associated with residual risk of coronary atherosclerotic heart disease. When compared with low-level apoB (≤0.66g/L), the multivariate adjusted RR and 95% CI of intermediate-level apoB (0.67-0.89g/L) and high-level apoB (≥0.90 g/L) were 1.16 (1.01, 1.33) and 1.31 (1.08, 1.60), respectively (P trend = 0.011). There was a 45% increased residual risk of coronary atherosclerotic heart disease per unit increment in natural log-transformed apoB (P trend＜0.05). However, higher levels of LDL-C were not significantly associated with residual risk of coronary atherosclerotic heart disease. When compared with low-level LDL-C (≤1.56mmol/L), the multivariate adjusted RR and 95% CI of intermediate-level LDL-C (1.57-2.30mmol/L) and high-level LDL-C (≥2.31mmol/L) were 0.99 (0.84, 1.15) and 1.10 (0.86, 1.42), respectively (P trend = 0.437). Similar results were observed in the stratified analyses and sensitivity analyses. No significant interactions were detected for both apoB and LDL-C (all Pinteraction > 0.05). Conclusions Elevated apoB are superior in assessing the residual risk of coronary atherosclerotic heart disease and severity of coronary atherosclerosis in participants with statin treatment.